Swimming by numbers: Age analysis of Olympic trials for 6 countries - Madge, R. (2016)
Analysis of the ages of Olympic Trials swimmers from different countries: Brazil, Russia, Japan, Canada, Great Britainn, Australia. Summary: The data shows median level for top level women swimmers is 20.4 about a year younger than the men`s median age of 21.5. However, median age does NOT mean peak performance age. If a country`s swimming performance health is tied to the age variation of its top swimmers, then Brazil is the healthiest of these 6 countries, and Canada is the least healthy. And, just as everyone already knew, sprinters tend to be the oldest swimmers, while distance swimmers tend to be among the youngest.